PENDEKATAN KRONOLOGI PADA NASKAH DOKUMENTER TELEVISI “ WANITA PEMAES” - Robby Yudistira; Dina Dwika Oktora (Institut Seni Indonesia Padangpanjang, 2022)
Paes is the art of decorating the face of traditional brides, especially Javanese brides. The creation of a television documentary script raises the topic of a performer from the side of his profession and life. The method used in the creation of this manuscript is the chronological method which divides each sequence according to the three stages of the chronological method, namely the first sequence as the introduction, the second sequence as the body or description and the third sequence as the closing. By applying this method to the script, the resulting impression will be more easily understood by the audience.